2022
DOI: 10.12688/f1000research.124904.2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of musculoskeletal disorders among dental healthcare providers: A systematic review and meta-analysis

Abstract: Background: Work-related musculoskeletal disorders (MSD) are common in dentistry due to the prolonged static work involved during patient care, making dental health care personnel vulnerable to musculoskeletal complaints. We aimed to pool the prevalence estimates of MSD among various dental healthcare providers, including dentists, dental students, dental hygienists, and auxiliaries. Methods: A systematic search of five databases was performed (Scopus, Embase, CINAHL, Web of Science, Dentistry & Oral Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…As per the location of the disorders, the most affected sites were the neck, the back, the lower back, the shoulder, the upper back and the wrist with a prevalence of 51%, 50%, 46%, 41%, 35% and 31%, respectively. 7 This is the first attempt to calculate the prevalence of CTS among dentists, through a systematic review. We do not have previously published data to compare our pooled estimate with.…”
Section: Discussionmentioning
confidence: 99%
“…As per the location of the disorders, the most affected sites were the neck, the back, the lower back, the shoulder, the upper back and the wrist with a prevalence of 51%, 50%, 46%, 41%, 35% and 31%, respectively. 7 This is the first attempt to calculate the prevalence of CTS among dentists, through a systematic review. We do not have previously published data to compare our pooled estimate with.…”
Section: Discussionmentioning
confidence: 99%
“…The total score of neck, trunk, and leg analysis ranged from 3 to 14, with higher values identifying riskier lower limb posture. Finally, a final score [1][2][3][4][5][6][7] was calculated and classified as follows:…”
Section: Posture Assessment Modalitymentioning
confidence: 99%
“…1 They constitute one of the most significant occupational health issues for dental professionals. 1 A recent systematic review and metaanalysis revealed that prevalence rates of MSK disorders range from 11% to 98% among dental providers, with the neck being the most affected area (58.5%, 95% confidence interval [CI] 46.0-71.0), followed by the lower back (56.4%, 95% CI 46.1-66.8) and shoulders (43.1%, 95% CI 30.7-55. 5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations